VALUE ADDED ANALYSIS ROBUSTA COFFEE IN HOME INDUSTRY PUTRA ADIRA CAP MAHKOTA RAJOKU IN KEPAHIANG REGENCY - Idsan, Rakha Satya; Taib, Gunarif; Hadiguna, Rika Ampuh (Jurnal Agroindustri, 2020)
This study aimed to measure the greater value obtained from Putra Adira Cap Mahkota Rajoku Ground Coffee in producing various ground coffee products. The research was conducted at the Putra Adira Cap Mahkota Rajoku Ground Coffee Business, which is a small-scale home industry that produces ground coffee products in Pelangkian Village, Kepahiang Regency, Bengkulu Province. Processed products from Robusta coffee analyzed were original ground coffee, ginger coffee, and pandanus coffee. The method of value added analysis used the Hayami calculation method. The results of the study showed that the added value of real coffee was Rp. 24,456,597 / kg or 82,174%, the added value of ginger coffee was Rp. 13,426,194 / kg or 29,967%, and the added value of pandanus coffee products was Rp. 18,638,833 / kg or 61,881%. Thus, the greatest added value was obtained in original coffee products because the higher the production, the higher the added value and the benefits obtained